Aspectos practicos y de ingenieria en la construccion y operacion de plantas de secado natural de yuca - Ospina Patiño, Bernardo (International Center for Tropical Agriculture, 1981)
The principal aspects that should be taken into account when constructing the min. infrastructure necessary for a natural cassava drying plant (installations, equipment, and tools) are summarized. The steps followed in the building of the drying floor, the chipping area, and the storage warehouse are given in detail. The need to fence off the drying area is indicated. Illustrations on the installations are included and the costs and theoretical aspects of the control of MC of cassava chips by a proximate method are annexed. (CIAT)